Oxygen behavior in germanium during melting laser thermal annealing. (February 2016) - Milazzo, R.; Impellizzeri, G.; Cuscunà, M.; De Salvador, D.; Mastromatteo, M.; La Magna, A.; Fortunato, G.; Priolo, F.; Privitera, V.; Carnera, A.; Napolitani, E.
Abstract: The diffusion of oxygen and its interactions with dopants during laser thermal annealing (LTA) in the melting regime is investigated. O is shown to penetrate from the surface and to diffuse during LTA both into germanium un- and also implanted with arsenic or boron. In the latter cases, the diffusion is unaffected by As, whereas it is significantly reduced by B. Accordingly, the electrical activation of As and B are respectively un-and anti-correlated with O. Therefore, it is concluded that O does not interact with As nor in the melt, nor in the solid phase during the cooling transient. On the other hand, the B–O clustering reported in literature to explain the B deactivation during LTA [Impellizzeri et al., J. Appl. Phys. 113(2013) 113505] occurs already in the liquid phase during the regrowth. Thence, the present data provide noteworthy results for the LTA implementation in future complementary metal-oxide devices.